Intellectual capital and sustainability in organizations of the Livestock Sector in Mexico - Marco Alberto Núñez Ramírez, Irma Guadalupe Esparza García, Karla Alejandra Garduño Realivazquez, Teodoro Rafael Wendlandt Amézaga,; Peñaherrera Larenas, Miltón Fabian; Lino Ferreira da Silva, Maicon Herverton (Opción, 2019)
The aim of this research is to determine the relationship between intellectual capital and sustainability in organizations of the livestock sector of southern Sonora, Mexico. A quantitative methodology was used with a correlative-explanatory approach. The results of the study suggest the existence of a positive and significant correlation between the variables under study (r = .538; p <.001). Moreover, only human capital predicts sustainability by 38%. Finally, the results of this study for the livestock sector differ from the contributions of other authors, who claim that relational capital is the most significant component of intellectual capital in terms of sustainability